2019
DOI: 10.1021/acs.jpclett.9b01824
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Nearly Isotropic Bright Excitons in InP/ZnSe Colloidal Quantum Dots

Abstract: The fine structure of exciton states in colloidal quantum dots (QDs) results from the compound effect of anisotropy and electron-hole exchange. By means of single-dot photoluminescence spectroscopy, we show that the emission of photo-excited InP/ZnSe QDs originates from radiative recombination of such fine-structure exciton states. Depending on the excitation power, we identify a bright exciton doublet, a trion singlet and a biexciton doublet line that all show a pronounced polarization. Fluorescence line 1 na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 28 publications
9
31
0
Order By: Relevance
“…More precisely, we used a laser with a linewidth of ∼300-μeV FWHM, which is narrow compared to the inhomogeneously broadened QD spectrum (150-meV FWHM; see Fig. S1) or even the homogeneously broadened single-QD spectrum measured in our previous work (3-meV FWHM [32]). By exciting on the low-energy side of the absorption spectrum, only the QDs with a high oscillator strength exciton state (bright state) that matches the energy of the excitation photons are excited.…”
Section: B Raman and Fluorescence Line Narrowing Spectroscopymentioning
confidence: 99%
“…More precisely, we used a laser with a linewidth of ∼300-μeV FWHM, which is narrow compared to the inhomogeneously broadened QD spectrum (150-meV FWHM; see Fig. S1) or even the homogeneously broadened single-QD spectrum measured in our previous work (3-meV FWHM [32]). By exciting on the low-energy side of the absorption spectrum, only the QDs with a high oscillator strength exciton state (bright state) that matches the energy of the excitation photons are excited.…”
Section: B Raman and Fluorescence Line Narrowing Spectroscopymentioning
confidence: 99%
“…We further note that the g factors we observed for PbS/CdS QDs are comparable in magnitude to those reported for CdSe, [ 34 ] CdSe/ZnS, [ 3 ] and InP/ZnSe QDs. [ 33 ] Increase of the g factor with transition energy has also been observed for CdSe [ 34 ] and InP/ZnS QDs. [ 35 ]…”
Section: Resultsmentioning
confidence: 93%
“…The Δ E xy values of 104–325 μeV are significantly smaller than the reported 0.5–3 meV splitting in CdSe QDs [ 32 ] and nearly quasi‐isotropic excitons recently reported in InP/ZnSe QDs. [ 33 ] These smaller Δ E xy values, together with an inability to observe any splitting in ensemble measurements, indicate that our PbS QDs maintain relatively good cubic symmetry. Furthermore, we note that these fine structure splittings also fall in the same order of magnitude as the 300–900 μeV splitting between the two lowest‐energy emitting states reported to have comparable lifetimes in the temperature‐dependent time‐resolved PL experiment on PbSe QDs.…”
Section: Resultsmentioning
confidence: 95%
“…Note that this finding is in line with published emission spectra of single InP/ZnSe QDs, where the biexciton emission was observed a mere 9.5 meV to the red of the exciton line. 29 Interestingly, as compared to the biexciton shift, the band-edge photoluminescence exhibits a…”
Section: Stimulated Emission -Model Descriptionmentioning
confidence: 99%
“…Ensemble-level and single-dot photoluminescence studies showed fine-structure properties and radiative lifetimes characteristic of strongly confined excitons. 25,28,29 Nevertheless, the presence of substitutional zinc that acts as a shallow hole trap was linked to the relatively broad, presumably trap-related, emission line of InP-based QDs. 30 While synthesisdependent variations of zinc incorporation may account for these differences, 31 this unclarity mostly calls for more insight in the opto-electronic properties of photo-excited InP-based QDs.…”
mentioning
confidence: 99%